DIE GROOT WOORD VAN DIE GEREGTIGHEID VAN GOD - Badenhorst, Theo (Scriptura, 1983)
The big word of God’s righteousness The Pauline concept of the righteousness of God has enjoyed a renewed interest amongst exegetes during the past two decades. After discussing the forensic, historical and laith aspect of the ședaqah concept and its relationship to the tồrah, the article focuses on the debate initiated by Käsemann and his pupils. Is the righteousness of God to be understood as a gift (gen. obiectivus) or a force (gen. subiectivus)? The author contends that this is a false alternative. The genitive should be understood as a gen. relationis in order to give due recognition to both the subjective and objective aspects. In so far as righteousness rests on God’s initiative, it is a gift which transcends individual existence. In so far as it is realized in faith, it acquires an individual dimension, but in such a way that the individual is incorporated in the encompassing field of God’s righteousness.